Heidegger on Poetry and Thought. From Metaphor to Dialogue - Ramazzotto, Nicola (Aesthetica Preprint, 2023)
The purpose of this paper is to analyze Heidegger’s critique for which the metaphysical conception of art is necessarily “metaphorical”, meaning a view that separates the spiritual and truthful content of art from the sensible and linguistic level in which it is expressed. The first part of this paper will analyse Heidegger’s critique of aesthetics with a particular focus on its metaphorical consideration of language. I will show how Heidegger considers Hegel to be the ultimate example of this view of art and language, I will try to trace the reasons for it, and I will emphasize the connection between metaphor and the end of art. In the second part, I will instead show Heidegger’s contrasting view of the relationship between poetry and language, which will be seen as two autonomous and equal responses to the event of the truth of being.